A guideline booklet for design intervention projects in crafts productive communities (Research, Society and Development, 2022)
The social and cultural devaluation of handicrafts demands its adaptation to a new market scenario. Its work together with design has been the strategy employed through design intervention programs. However, this process has not generated lasting results. Therefore, this research sought to build guidelines for the construction of new programs structured in a booklet. To this end, it developed an analytical-qualitative research with conversations with 100 artisans from 16 communities about the intervention programs in which they participated. As a result, the negative and positive points of the programs according to the artisans were presented. This problem involved (1) the project itself; (2) its execution; (3) content worked and (4) participants. The active participation of the artisans, from the design of the project to the execution of the workshops as workshop workers, stands out as fundamental. They were also emphasized as important contents and workload distribution of the workshops contextualized with the community. In addition to these direct results, it was also possible to conclude some characteristics of the community that facilitate and hinder the execution and maintenance of the actions of the intervention projects, such as the presence of active leadership (natural or built) and the understanding of the need and interest in changes. As an obstacle, the financial immediacy and low self-esteem of the artisans stand out. Given this information, some guidelines can be identified.